The Influence of Management Accounting Information Systems and Total Quality Management on Managerial Performance - Maulida, Maulida; Affan, Nurita (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
This study aims to determine the influence of management accounting information systems and total quality management on managerial performance at PT Tri Mandiri Selaras Daihatsu Samarinda. This study uses a quantitative approach. The population in this study is employees at PT Tri Mandiri Selaras Daihatsu Samarinda. The sampling technique used a saturated sampling method where the entire population is sampled, with a total of 41 samples. This study uses multiple linear regression analysis using the IBM SPSS (Statistical Package for Social Science) version 27 application analysis tool. The results of this study indicate that the management accounting information system has a positive and significant effect on managerial performance, and total quality management has a positive and significant effect on managerial performance